A genome-wide association study identifies an osteoarthritis susceptibility locus on chromosome 7q22. - Kerkhof, H; Lories, R; Meulenbelt, I; Jonsdottir, I; Valdes, A; Arp, P; Ingvarsson, T; Jhamai, M; Jonsson, H; Stolk, L; Thorleifsson, G; Zhai, G; et al. (2010)
OBJECTIVE: To identify novel genes involved in osteoarthritis (OA), by means of a genome-wide association study. METHODS: We tested 500,510 single-nucleotide polymorphisms (SNPs) in 1,341 Dutch Caucasian OA cases and 3,496 Dutch Caucasian controls. SNPs associated with at least 2 OA phenotypes were analyzed in 14,938 OA cases and approximately 39,000 controls. Meta-analyses were performed using the program Comprehensive Meta-analysis, with P values <1 x 10(-7) considered genome-wide significant. RESULTS: The C allele of rs3815148 on chromosome 7q22 (minor allele frequency 23%; intron 12 of the COG5 gene) was associated with a 1.14-fold increased risk (95% confidence interval 1.09-1.19) of knee and/or hand OA (P = 8 x 10(-8)) and also with a 30% increased risk of knee OA progression (95% confidence interval 1.03-1.64) (P = 0.03). This SNP is in almost complete linkage disequilibrium with rs3757713 (68 kb upstream of GPR22), which is associated with GPR22 expression levels in lymphoblast cell lines (P = 4 x 10(-12)). Immunohistochemistry experiments revealed that G protein-coupled receptor protein 22 (GPR22) was absent in normal mouse articular cartilage or synovium. However, GPR22-positive chondrocytes were found in the upper layers of the articular cartilage of mouse knee joints that were challenged with in vivo papain treatment or methylated bovine serum albumin treatment. GPR22-positive chondrocyte-like cells were also found in osteophytes in instability-induced OA. CONCLUSION: Our findings identify a novel common variant on chromosome 7q22 that influences susceptibility to prevalence and progression of OA. Since the GPR22 gene encodes a G protein-coupled receptor, this is potentially an interesting therapeutic target.